Edukasi Alat Tangkap Ramah Lingkungan dan Regulasi Perikanan: Upaya Meningkatkan Kesadaran Masyarakat dalam Pengelolaan Sumber Daya Perikanan di Desa Lero - Kurnia, Muhammad; Adib Daulat Irsyad (Abdi Techno, 2025)
The Community Service Program (KKN) aims to increase awareness of the coastal community of Lero Village regarding the importance of using environmentally friendly fishing gear and enhancing knowledge about fisheries regulations. The improper use of fishing gear can damage the ecosystem and reduce catch yields. In this extension activity, education was provided on various environmentally friendly fishing gear and explanations of the regulations that must be adhered to to avoid violating provisions that harm the environment and the economy of the community. The implementation method of the program includes outreach and demonstrations in the field regarding the use of environmentally friendly fishing gear. The results show an increase in community understanding regarding the importance of maintaining the balance of the marine ecosystem through the application of appropriate fishing gear and awareness of fisheries regulations. This program has also been successful in encouraging changes in the attitudes and mindsets of fishermen to begin transitioning to more sustainable fishing practices. It is hoped that through this program, the Lero Village community can preserve the sustainability of marine resources and improve their economic welfare sustainably in the future.